The application of associative methods to analyze the impact of Christian learning management and classroom management on academic achievement - Berdinata Massang; Horasman Perdemunta Munthe; Natanael Chandra; Hotliong Verawaty (Jurnal Konseling dan Pendidikan, 2025)
This study is motivated by the theoretical approach and the suboptimal internalization of Christian values, which affects students' academic achievement. The purpose of this research is to analyze the impact of Christian learning management and classroom management, both partially and simultaneously, on students' academic achievement. The research uses a quantitative associative approach with proportionate stratified random sampling, involving 253 students from four study programs at the Faculty of Christian Education Science, IAKN Manado. The instrument used is a Likert-scale questionnaire tested for validity (r count > 0.294) and reliability (Cronbach’s Alpha 0.913 and 0.858), along with data from GPA. Data analysis was conducted using multiple linear regression with SPSS 25 after passing classical assumption tests. The results show that both Christian learning management (t=14.885; p<0.001) and classroom management (t=14.990; p<0.001) significantly influence academic achievement, with both variables contributing 63.8% (F=219.851; R²=0.638) to the students' academic performance. These findings highlight the importance of effective management in both learning and classroom settings. The practical implication is the need for faculty to enhance their ability to manage learning and classrooms holistically. Future studies should explore additional variables that influence academic achievement and use a longitudinal design.